Learning to teach and professional identity: images of personal and professional recognition (2014)
This study aims to investigate how pre-service teachers construct their professional identities from the interplay between participation in a teacher community and their systems of knowledge and beliefs. A group of six Colombian pre-service teachers in the final stage of their five-year teacher education programme were the research participants. Interviews, stimulated recall, and on-line blogs as methods of data collection, and content and conversation analyses as the analytical approaches, were used. The findings reveal that while the process of learning to teach is individually constructed and experienced, it is socially negotiated.Este estudio tiene como objetivo investigar cómo los maestros en formación construyen su identidad profesional desde la relación de su experiencia cómo miembros de una comunidad educativa y sus sistemas de conocimiento pedagógico. Los participantes fueron seis maestros de lenguas colombianos quienes se encuentran en la etapa final de formación de su programa de licenciatura en idiomas. Los métodos de recolección de información fueron entrevistas, estimulación retrospectiva y blogs en línea, mientras que el análisis del contenido y de la conversación fueron los enfoques analíticos usados. Los resultados señalan que mientras el proceso de aprender a enseñar se construye y se vive en forma individual, este se negocia socialmente.